2014
DOI: 10.1111/j.2047-2927.2014.00248.x
|View full text |Cite
|
Sign up to set email alerts
|

H3K79 methylation directly precedes the histone‐to‐protamine transition in mammalian spermatids and is sensitive to bacterial infections

Abstract: SUMMARYIn both mammalian and Drosophila spermatids, the completely histone-based chromatin structure is reorganized to a largely protamine-based structure. During this histone-to-protamine switch, transition proteins are expressed, for example TNP1 and TNP2 in mammals and Tpl94D in Drosophila. Recently, we demonstrated that in Drosophila spermatids, H3K79 methylation accompanies histone H4 hyperacetylation during chromatin reorganization. Preceding the histone-to-protamine transition, the H3K79 methyltransfera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
48
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 59 publications
(65 reference statements)
9
48
1
Order By: Relevance
“…Hence, these histone modifications might be involved in both transcription and the histone-to-protamine transition. The data presented here are contradictory to our recently published data [2] and to other published data showing that histones are unacetylated in most round spermatids [25]. This difference in our current observations could be explained by the use of 4% F-PBS to fix testes, which, as mentioned above, in many cases allows a more sensitive immunohistochemical detection of proteins.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…Hence, these histone modifications might be involved in both transcription and the histone-to-protamine transition. The data presented here are contradictory to our recently published data [2] and to other published data showing that histones are unacetylated in most round spermatids [25]. This difference in our current observations could be explained by the use of 4% F-PBS to fix testes, which, as mentioned above, in many cases allows a more sensitive immunohistochemical detection of proteins.…”
Section: Discussioncontrasting
confidence: 57%
“…In mice, active RNA polymerase II was observed in each germ cell up to steps 8-9 spermatids but not in later spermatids ( Fig. 2A) [2]. TAF2 was detected in the nuclei of spermatocytes and spermatids up to step 9 (Fig.…”
Section: Several Different Tafs and Bromodomain-containing Proteins Omentioning
confidence: 99%
See 2 more Smart Citations
“…Dottermusch-Heidel et al (92) reported that the bacterial infections lead to the premature emergence of trimethylated H3K79 and hyperacetylated H4, which simultaneously occur with the transition protein TNP1. In contrast, they were never observed in the spermatids of infected rats.…”
Section: The Effects Of Bacterial Infection On Sperm Chromatin Condenmentioning
confidence: 99%